Implementation of Augmented Reality and panoramic view for interior house design - Tan, Pei Lin (Universiti Malaysia Sarawak (UNIMAS), 2015)
The main purpose of this study is to implement Augmented Reality (AR) and panoramic view in interior house design. AR is defined as the overlapping of threedimensional (3D) virtual objects with real environment. Iteration and Incremental Development (IID) application development process model was used to develop the application. Unity3D is the main platform used to build the application. Cooperative evaluation was carried out to test the functionality of the application. Three respondents who have a background in Human Computer Interaction as well as past experiences in using several mobile applications were chosen to be respondents of this study. The application was divided into several stages and was built from one component to another until the whole application was completed. This application was easy to use and gained positive feedback from each respondent. Implementation of AR and panoramic view in interior house design is still a new trend. Hence, further research and development can be carried out to improve its application.